Seroprevalence of spotted fever group (SFG) rickettsiae infection in domestic ruminants in Khartoum State, Sudan. Issue 2 (21st February 2017) - Eisawi, Nagwa M.; Hassan, Dina A.; Hussien, Mohammed O.; Musa, Azza B.; El Hussein, Abdel Rahim M.
Abstract: Spotted fever group (SFG) rickettsiosis is caused by obligatory intracellular Gram‐negative bacteria that belong to the genus Rickettsia . Ticks belonging to the family Ixodidae can act as vectors, reservoirs or amplifiers of SFG rickettsiae. This study was conducted to estimate the seroprevalence of SFG rickettsioses in cattle, sheep and goats from Khartoum State, Sudan. Blood samples were collected from a total of 600 animals (sheep, goats and cattle) from 32 different farms distributed in three locations in Khartoum State during the period January to December 2012. Sera were tested for antibodies against SFG rickettsiae using IFAT. The prevalence of seropositivity was 59.3% in sheep, 60.1% in goats and 64.4% in cattle. Season was significantly ( P < 0.05) associated with seroprevalence of SFG rickettsiae in cattle during winter. The SFG rickettsiae antibodies prevalence was significantly higher in female compared with male in sheep, but there were no significant differences between male and female in either cattle or goats. The prevalence was significantly higher in adult animals compared with young in both sheep and goats. With regard to management system, there was a significant difference in the prevalence in cattle raised in closed system compared with those raised in semi‐intensive system. In contrast, there was significant difference in the seroprevalence of SFG in sheep where the prevalence was higher in the sheep raised in semi‐intensive system compared with those raised in close system. There was no significant difference in the seroprevalence in goats with regard to management systems. The unexpected high prevalence of SFG rickettsia antibodies in domestic ruminants sera suggest that the veterinary and public health impact of these agents in Sudan need further evaluation especially in humans. Abstract : The prevalence was 59.3% in sheep, 60.1% in goats and 64.4% in cattle. Season was significantly ( P < 0.05) associated with seroprevalence of spotted fever group (SFG) rickettsiae in cattle during winter. The SFG rickettsiae antibodies rate was significantly highest in female compared with male in sheep. The prevalence was significantly highest in young animals compared with adults in both sheep and goats. With regard to management system, there was a significant difference in the prevalence in cattle raised in closed system compared with those raised in semi‐intensive system.